Waste-based composites using post-industrial textile waste and packaging waste from the textile manufacturing industry for non-structural applications - R.M.N. Sulochani; R.A. Jayasinghe; G. Priyadarshana; A.H.L.R. Nilmini; M. Ashokcline; P.D. Dharmaratne (Sustainable Chemistry for the Environment)
The textile industry significantly contributes to environmental pollution, generating substantial amounts of waste. The prevailing linear model exacerbates this issue, accumulating a significant portion of the waste in landfills. This research aimed to tackle these challenges by developing value-added composites from post-industrial textile waste and packaging materials, for non-structural building applications. To achieve this, shredded polyester textile waste fibers served as the reinforcement, while waste packaging was used as the matrix. Varying fiber-matrix weight percentages seven composite types were developed. The physical, mechanical, and thermal properties of the composites were evaluated. The findings indicated that these composites exhibited properties comparable to those of commercial partition boards. Notably, composites with fiber weight percentages of 7.5 % and 10 % demonstrated the most favorable performance among the tested variations. Emphasizing the application of sustainable chemistry, this study highlights the potential of these composites to develop substitute materials for non-structural building applications. Moreover, it presents a promising solution to address the textile waste management challenge and value-added materials for the construction industry in a developing context.